Direct 3D printing of a graphene oxide hydrogel for fabrication of a high areal specific capacitance microsupercapacitor. Issue 50 (17th September 2019) - Yun, Xiawei; Lu, Bingchuan; Xiong, Zhiyuan; Jia, Bo; Tang, Bo; Mao, Henan; Zhang, Ting; Wang, Xiaogong
Abstract : This work demonstrates successful fabrication of a high areal specific capacitance micro-supercapacitor via direct 3D printing of a graphene oxide hydrogel. Abstract : In this work, we demonstrate that a graphene oxide (GO) hydrogel with unique rheological properties, such as high storage modulus, shear-thinning nature and fast viscosity recovery, is highly suitable as an ink for three dimensional (3D) printing. The results show that the GO ink has the characteristics of both gel and viscous liquid, where the gel–liquid transition depends on the shear rate and shear strain amplitude. In the extrusion and printing process, the ink shows significant shear thinning and rapid viscosity recovery after cessation of shearing, which are desirable for 3D printing through direct ink writing (DIW). A suitable scanning speed and extrusion speed were determined to construct a precise 3D structure. After the reduction, the RGO electrode with hierarchical porous structures is stable, of higher precision, and loaded with more of the effective materials per unit area. The 3D printed micro-supercapacitors (MSCs) with interdigitated architecture exhibit a high areal specific capacitance of 101 mF cm −2 at a current density of 0.5 mA cm −2 and 111 mF cm −2 at a scan rate of 10 mV s −1, which are superior compared with most of the reported MSCs of carbon-based materials.